Urgensi Mediasi dalam Meminimalisir Perkara Perceraian di Pengadilan Agama Bangko Kabupaten Merangin - Ibrahim Ibrahim; Hindra Masdianto (Dinasti Review, 2022)
Abstract: The purpose of this study was to find out the mediation process in minimizing divorce cases at the Bangko Religious Court as stipulated in the statutory provisions regarding mediation, as well as the factors inhibiting the success of mediation in minimizing the divorce rate in the Religious Courts. This study uses a normative juridical approach which is qualitative with data collection methods through observation, interviews, and documentation. Based on the research conducted, the results of this study are as follows: (1). The process of carrying out mediation at the Bangko Religious Court, law enforcement, the role of the mediator, synchronizing the parties, providing facilities and infrastructure and culture; (2). There are several reasons for the inhibiting factors for successful mediation at the Bangko Religious Court, namely: the small number of judges, the parties agreeing to a divorce, the intervention of a third party, the absence of one of the parties, and the long distance; (3). The judge's efforts for the success of mediation in minimizing divorce cases at the Bangko Religious Court are, increasing the number of judges and non-judge mediators, judges providing advice to the parties, and presenting families from both parties who are in a case. Abstrak: Tujuan penelitian ini adalah untuk mengetahui proses mediasi dalam meminimalisir perkara perceraian di Pengadilan Agama Bangko sebagaimana ketentuan perundang-undangan tentang mediasi, serta bagaimana fakto-faktor penghambat keberhasilan mediasi dalam meminimalisir angka perceraian di Pengadilan Agama. Penelitian ini menggunakan pendekatan yuridis normatif yang sifatnya kualitatif dengan metode pengumpulan data melalui observasi, wawancara, dan dokumentasi. Berdasarkan penelitian yang dilakukan, maka hasil penelitian ini adalah sebagai berikut: (1). Proses pelaksanaan mediasi di pengadilan agama bangko, penegak hukum, peran mediator, sinkronisasi para pihak, menyediakan sarana dan prasarana dan budaya.; (2). Factor-faktor penghambat keberhasilan mediasi di Pengadilan Agama Bangko ada beberapa sebab yaitu : jumlah hakim yang sedikit, para pihak beriktikat untuk bercerai, campur tangan pihak ketiga, tidak hadirnya salah satu pihak dan jarak tempuh yang jauh.; (3). Upaya hakim untuk keberhasilan mediasi dalam meminimalisir perkara perceraian di Pengadilan Agama Bangko adalah, penambahan jumlah hakim dan mediator non hakim, hakim memberikan nasehat kepada para pihak dan menghadirkan keluarga dari kedua belah pihak yang sedang berperkara.